2018
DOI: 10.1016/j.joca.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

An observational analysis of discontinuation and non-publication of osteoarthritis trials

Abstract: If discontinuation and non-publication rates in osteoarthritis trials continue to be sub-optimal, already scarce research resources will continue to be wasted. One possible explanation for the witnessed nonpublication that warrants further investigation is the issue of publication bias or selective reporting bias, two known problems that decrease research productivity and ethics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 25 publications
5
22
0
Order By: Relevance
“…Although we used multiple search methods, we were unable to find email contacts for twothirds of 63 unpublished trials included in our study. Consistent with our findings, Scott et al 21 had similar difficulties when attempting to locate contact information of the investigators, only finding 39.4% of email addresses. 20 Up-to-date monitoring of trial status on trial registries and ensuring that each trial publication and principal investigator's contact information are linked to the registry might alleviate some difficulties in accessing data from published and nonpublished RCTs.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Although we used multiple search methods, we were unable to find email contacts for twothirds of 63 unpublished trials included in our study. Consistent with our findings, Scott et al 21 had similar difficulties when attempting to locate contact information of the investigators, only finding 39.4% of email addresses. 20 Up-to-date monitoring of trial status on trial registries and ensuring that each trial publication and principal investigator's contact information are linked to the registry might alleviate some difficulties in accessing data from published and nonpublished RCTs.…”
Section: Discussionsupporting
confidence: 92%
“…These results merit further research to define contributing factors because they are not consistent with previous works in other medical specialties. For example, a 2018 orthopedic study 21 found reasons for trial discontinuation for 29 of 30 (97%) discontinued trials related to osteoarthritis. Moreover, all 273 osteoarthritis RCTs (97%) reported the reasoning for trial discontinuation on ClinicalTrials.gov.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations